Randomized Noninferiority Trial of Expectant Management versus Early Treatment of Patent Ductus Arteriosus in Preterm Infants - Potsiurko, Solomiia; Dobryanskyy, Dmytro; Sekretar, Lesya; Salabay, Zoryana (American Journal of Perinatology, 2022)
Objective The study aimed to investigate, whether expectant management is noninferior to early patent ductus arteriosus (PDA) treatment with regard to the composite of mortality and/or incidence of bronchopulmonary dysplasia (BPD) in very preterm infants.Study design A total of 208 very preterm infants of the gestational age <32 weeks, birth weight <1,500 g, chronological age <72 hours, and PDA >1.5 mm were randomized between the treatment or expectant management groups. Both, the intention-to-treat and per-protocol analyses were performed.Results A total of 104 (50%) patients received rectal ibuprofen (n = 52) or intravenous acetaminophen (n = 52) within first 72 hours of life. In 104 (50%) infants, expectant management was used. Eight of them (8%) received rescue treatment at the median age of 7 (range: 6–13) days. PDA closure rates by the 10th day of life were 81% (n = 84) in the treatment arm, and 58% (n = 60) in the expectant management arm (p < 0.01). The median age at the time of ductus closure was 5 (range: 5–6) days in the treatment arm and 8 (range: 6–11) days in the expectant management arm (p < 0.01). At the time of discharge, ductus was closed in 83% of treated infants and in 78% of patients who were managed expectantly (p > 0.05). No significant difference between the groups was found for the primary clinical outcomes, BPD/death, or the secondary outcomes at a postmenstrual age of 36 weeks or discharge.Conclusion Expectant management is noninferior to early PDA treatment for reducing the incidence of death/BPD. Compared with the expectant management, early pharmacological treatment provides more frequent and faster PDA closure in preterm infants with gestational age <32 weeks, but it neither reduces morbidity nor improves survival rates.Key Points
Keywords: patent ductus arteriosus; early PDA treatment; noninferior; expectant management; perinatal outcomes